Being and becoming - Markou, Smaro (Murmurations: Journal of Transformative Systemic Practice, 2023)
This paper is a personal testimony, a short account of my experience of suffering from the side effects of covid-19 on underlying heart disease. Writing from within moments of pain and agony, I unfold my inner journey to the void and back. Reflecting on that journey I offer my thoughts, born upon my contact with therapists, doctors, and nurses in the hospitals where I was treated, and my inner dialogue with the voices of many people who have nourished my thinking and practice all these years. Traveling through the unknown conditions of my illness and recovery, who I am and who I am becoming personally and professionally, have been in constant movement and intra-action. From this place I offer some reflections on identity, power and on being a therapist.